Utilizing heat from rice hull biochar production for steam pasteurization of mushroom fruiting bags. Issue 1 (1st January 2018) - Orge, Ricardo F.; Leal, Lolita V.
Abstract: Smallholder rice-based farmers are among those who are significantly affected by climate change in the Philippines. Their livelihoods are at risk once the country is visited by extreme events like strong typhoons, intense floods and severe droughts. One of the proven strategies to help enhance their resilience to these events is to diversify their farming activities and sources of income, not just relying on the climate sensitive rice production. Mushroom production, which utilizes rice straw as substrate, is one of the popular rice-based income-generating activities now being promoted by PhilRice and other government agencies. The existing practice makes use of wood as fuel in the steam pasteurization of the mushroom fruiting bags (MFBs) which are contained in 200-l steel drums. In this study, an improved, safe, and highly sustainable system of pasteurizing the MFBs was developed, utilizing the heat generated from the carbonization of rice hull. This system not only eliminates the use of wood as fuel which encourages cutting of trees but also co-produce rice hull biochar which has a variety of uses in diversified and integrated rice-based farming systems.